Angela Condello in dialogue with Chiara Bottici. Difference Feminism and Anarchafeminism. Perspectives on Gender Justice - Condello, Angela; Bottici, Chiara (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2024)